2012
DOI: 10.3892/ijmm.2012.1206
|View full text |Cite
|
Sign up to set email alerts
|

Novel rotundic acid derivatives: Synthesis, structural characterization and in vitro antitumor activity

Abstract: Abstract. Six novel rotundic acid (RA, 1) derivatives 4a-4f modified at the 28-COOH position were synthesized, and their structures were confirmed by IR, MS,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…(2011) found that RA displayed anti-inflammatory effects in murine microglial cells [ 8 ]. The cytotoxic activities of RA toward human hematoma cell line (HepG2), malignant melanoma cell line (A375), breast cancer cell line (MCF-7), and colon cancer cell line (HT-29) have been observed [ 9 , 10 ]. Although those previous studies suggest that MEA and RA are natural compounds with several bio-activities, less information is available regarding the in vivo protective activities of MEA or RA against diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…(2011) found that RA displayed anti-inflammatory effects in murine microglial cells [ 8 ]. The cytotoxic activities of RA toward human hematoma cell line (HepG2), malignant melanoma cell line (A375), breast cancer cell line (MCF-7), and colon cancer cell line (HT-29) have been observed [ 9 , 10 ]. Although those previous studies suggest that MEA and RA are natural compounds with several bio-activities, less information is available regarding the in vivo protective activities of MEA or RA against diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…[45] The phytochemical RA, a biologically active compound, has been extracted from plants of the Ilex genus. [46,47] A few species of Ilex, including Ilex rotunda, [46] Ilex purpureai, [48] Ilex chinensis, [47,49] Ilex integra, [50,51] Ilex doniana [52] have been recognized in several literatures and are known for their therapeutic benefits. These plants are commonly found in East Asia, especially in Japan, China, Korea, Vietnam, and Taiwan, where local people have traditionally used them to cure different ailments.…”
Section: Botanical Sourcesmentioning
confidence: 99%
“…Camelina sativa - [55] Enkianthus campanulatus Leaves [56] Euscaphis japonica Leaves [57] Glochidion obliquum Leaves [58] Ilex chinensis leaves [47,49] I. integra Fruit [50,51] I. rotunda, I. purpurea Seeds [46,48] I. doniana Leaves [52] Mitragyna diversifolia Stem bark [59…”
Section: Plant Name Plant Part Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotundic acid (RA), a plant-derived and ursane-type pentacyclic triterpene acid, was identified as a major active ingredient of IRC and has been shown to exert extensive pharmacological effects, including antimicrobial [ 3 , 4 ], anti-inflammatory [ 5 ], anticancer [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] ], and lipid-decreasing effects [ 14 ]. It has also been proven to alleviate type 2 diabetes and its complications by improving the composition of the gut microbiota [ 15 ].…”
Section: Introductionmentioning
confidence: 99%